Electrophysiologic effects of agmatine on pacemaker cells in sinoatrial node of rabbits. - Li Xiao-tao; Fan Zhen-zhong; He Rui-rong (Acta Pharmacologica Sinica, 2016)
AIM: To study the electrophysiologic effects of agmatine (Agm) on pacemaker cells in sinoatrial (SA) node. METHODS: Parameters of action potential (AP) in SA node were recorded using intracellular microelectrode technique. RESULTS: Agm not only slowed down the amplitude of action potential (APA), maximal rate of depolarization (Vmax), velocity of diastolic (phase 4) depolarization (VDD), and rate of pacemaker firing (RPF), but also prolonged 90% duration of action potential (APD90) in a concentration-dependent manner. The effects of Agm (10 mmol.L-1) could be blocked completely by pretreatment with idazoxan (0.15 mmol.L-1), an alpha 2-adrenergic receptor (alpha 2-AR) and imidazoline receptor (IR) antagonist. Pretreatment with NG-nitro-L-arginine methyl ester (L-NAME, 1 mmol.L-1), an NOS inhibitor, did not affect the electrophysiologic effects of Agm on pacemaker cells in SA node. Elevation of Ca2+ concentration (5 mmol.L-1) in perfusate antagonized the effects of Agm (10 mmol.L-1). Lemakalim (Lem, 30 mumol.L-1), an opener of ATP-sensitive potassium channels, partially inhibited the prolonging effect of Agm on repolarization. CONCLUSION: The electrophysiologic effects of Agm on pacemaker cells in SA node were likely attributed to the reduction in calcium influx and potassium efflux and mediated by alpha 2-AR and IR.